KRAS G12D mutation in Brunner gland adenoma. Issue 1 (27th January 2023) - Ortega, Mahatma; Sparks, Jessica; Lichy, Jack; Nava, Victor E
Abstract : Brunner gland lesions (BGLs) encompass benign proliferations of the homonymous glands and have been designated as hyperplasia, adenoma (BGA), hamartoma or nodule. In general terms, lesions larger than 0.5 cm are considered true neoplasia with unknown malignant potential and unclear pathogenesis. Genetic alterations have seldom been reported in BGL, and include SMAD4/DPC4 and LRIG1, but not KRAS (Kirsten rat sarcoma viral oncogene homologue) to the best of our knowledge. We present the case of a man in his 60s, evaluated for iron deficiency anaemia harbouring a 1.5 cm BGA found by duodenoscopy. Immunohistochemistry failed to reveal microsatellite instability, and next-generation sequencing revealed a KRAS G12D point mutation.